2019
DOI: 10.3389/fchem.2019.00784
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Engineered PtPdMo Alloy With Enhanced Antioxidant Activity for Intestinal Injury

Abstract: Radiotherapy is the mainstay for abdomen and pelvis cancers treatment. However, high energy ray would inflict gastrointestinal (GI) system and adversely disrupt the treatment. The anti-oxidative agents provide a potential route for protecting body from radiation-induced injuries. Herein, highly catalytic nanocubes with dislocation structure are developed for treatment of intestinal injury. Structural and catalytic properties show that Mo incorporation can enhance antioxidant activity by dislocation structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…609 Besides, Long et al further introduced Mo into the PtPd nanocubes to improve their ROS scavenging ability. 610 The prepared ternary alloy PtPdMo nanocubes could effectively protect healthy cells from γ-ray irradiation and improve the survival rate of irradiated mice by 50%, which was higher than those pre-treated with Pt (30%) and PtPd (40%) counterparts. In addition, Wang et al incorporated rhodium (Rh) into PtPd nanocubes to prepare ternary PtPdRh nanocubes for investigation of their free radical scavenging capability (Fig.…”
Section: Feature Application Of Precision Radiotherapy For Radioprote...mentioning
confidence: 87%
“…609 Besides, Long et al further introduced Mo into the PtPd nanocubes to improve their ROS scavenging ability. 610 The prepared ternary alloy PtPdMo nanocubes could effectively protect healthy cells from γ-ray irradiation and improve the survival rate of irradiated mice by 50%, which was higher than those pre-treated with Pt (30%) and PtPd (40%) counterparts. In addition, Wang et al incorporated rhodium (Rh) into PtPd nanocubes to prepare ternary PtPdRh nanocubes for investigation of their free radical scavenging capability (Fig.…”
Section: Feature Application Of Precision Radiotherapy For Radioprote...mentioning
confidence: 87%
“…In a previous review, we introduced many nanoradioprotectors. Thereafter, new nanoradioprotectors, such as ultrasmall Au‐MoS 2 clusters, [ 177 ] PVP‐coated PtPdMo nanocubes, [ 178 ] PtPd nanocrystals, [ 179 ] naturally derived PHA‐L protein NPs, [ 180 ] CeO 2 /Mn 3 O 4 nanocrystals, [ 57 ] pH‐triggered Mn clusters, [ 181 ] polydopamine@arginine–chitosan (thalidomide) nanodrugs, [ 58 ] Nb 2 C‐PVP nanosheets, [ 31 ] CNSI, [ 32 ] and the GLSO@P188/PEG400 nanosystem, [ 37 ] have emerged. Their emergence enriched the treatment pattern in the radioprotection field.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PtPdMo nanocubes with multienzyme activities were synthesized by dislocation engineering. 92 The results showed that PtPdMo nanocubes reduced the excess ROS to H 2 O, as well as repairing organ damage by inhibiting intestinal epithelial apoptosis and reducing DNA strand breaks. Meanwhile, Wang et al designed PtPdRh hollow nanocubes (HNCs) not only to exhibit the effects of POD-and CAT-like activities, but also possess the effect of scavenging •OH (Figure 3).…”
Section: Catalytic Nanozyme For Radiation Protectionmentioning
confidence: 96%
“…The 30 day survival rate exhibited that PtPd nanocubes prolonged the survival time of mice, and the survival rate of mice after 7.2 Gy irradiation increased from 0% to 30%. Recently, PtPdMo nanocubes with multienzyme activities were synthesized by dislocation engineering . The results showed that PtPdMo nanocubes reduced the excess ROS to H 2 O, as well as repairing organ damage by inhibiting intestinal epithelial apoptosis and reducing DNA strand breaks.…”
Section: Catalytic Nanozyme For Radiation Protectionmentioning
confidence: 99%